2021
DOI: 10.1111/tbed.14208
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of antibodies against SARS‐CoV‐2 in dogs and cats, Thailand

Abstract: Coronavirus disease of 2019 (COVID-19) caused by severe acute respiratory syndrome virus type 2 (SARS-CoV-2) is an emerging severe acute respiratory disease affecting global human health. In this study, a large-scale serological survey of antibodies against SARS-CoV-2 in dogs and cats was conducted during the first and second waves of COVID-19 outbreaks in Thailand, from April to December 2020. A total of 3215 serum samples were collected from dogs (n = 2102) and cats (n = 1113) living in Bangkok and in the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 42 publications
6
39
1
Order By: Relevance
“…Two of them, conducted in Italy, revealed a prevalence of 1% (1/105) and 0% (0/99) (Spada et al., 2021 ; Stranieri et al., 2021 ). Another one, performed in Thailand, found a prevalence of 0.36% (4/1,112) (Udom et al., 2021 ). Moreover, an investigation of 17 cats with owners that previously tested positive for SARS‐CoV‐2 was performed (Neira et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two of them, conducted in Italy, revealed a prevalence of 1% (1/105) and 0% (0/99) (Spada et al., 2021 ; Stranieri et al., 2021 ). Another one, performed in Thailand, found a prevalence of 0.36% (4/1,112) (Udom et al., 2021 ). Moreover, an investigation of 17 cats with owners that previously tested positive for SARS‐CoV‐2 was performed (Neira et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive sera were collected from the owners with COVID-19, pet hospitals, and stray ani mals [98]. The same result in Thailand showed that 1.66% of the sera collected from dogs during the outbreak were positive to SARS-CoV-2 antibodies [92].…”
Section: Sars-cov-2 Infections In Dogsmentioning
confidence: 76%
“…However, all nasopharyngeal and anal swabs were negative for SARS-CoV-2 viral RNA [27]. In Thailand, a serological survey was conducted on cats from April to December 2020 and showed that 4 of 1112 sera antibodies were positive to antibodies against SARS-CoV-2 [92].…”
Section: Clinicalmentioning
confidence: 99%
“…Although such zoonotic disease has probably disseminated mainly by human-to-human transmission, the existence of hundreds of millions of companion animals living closely with humans raises the question of their potential role in the outbreak [ 1 , 2 , 3 , 4 ]. Accordingly, several studies have been recently performed in dogs and cats in many countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], demonstrating their susceptibility to this infection. However, it is important to acknowledge that the majority of these studies are serological and/or molecular surveys primarily aimed at evaluating the transmission of SARS-CoV-2 among domestic animals, not the related clinical compromise [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies have been recently performed in dogs and cats in many countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], demonstrating their susceptibility to this infection. However, it is important to acknowledge that the majority of these studies are serological and/or molecular surveys primarily aimed at evaluating the transmission of SARS-CoV-2 among domestic animals, not the related clinical compromise [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Consequently, to date, there is little evidence to determine how commonly SARS-CoV-2 naturally infected dogs and cats develop clinical signs and to characterise the clinical manifestations of the viral infection in these species.…”
Section: Introductionmentioning
confidence: 99%